Children's and adolescents' sedentary behaviour in relation to socioeconomic position. Issue 10 (13th July 2013) - Coombs, Ngaire; Shelton, Nicola; Rowlands, Alex; Stamatakis, Emmanuel
Abstract : Background: Sedentary behaviour is an emerging cardiometabolic risk factor in young people. Little is known about how socioeconomic position (SEP) and sedentary behaviour are associated in children and adolescents. This study examines associations between SEP and sedentary behaviour in school-age children and adolescents. Methods: The core sample comprised 3822 Health Survey for England 2008 participants aged 5–15 years with complete information on SEP (household income, head of household occupational social class and area deprivation) and self-reported sedentary time (television viewing and other sitting during non-school times). Accelerometer-measured total sedentary time was measured in a subsample (N=587). We examined multivariable associations between SEP (including a composite SEP score) and sedentary time using generalised linear models, adjusting for age, sex, body mass index, physical activity, accelerometer wear time and mutually adjusting for the other SEP indicators. Results: Participants in the highest SEP category spent 16 min/day less (95% CI 6 to 25, p=0.003) watching TV than participants in the lowest SEP category; yet they spent 7 (2 to 16, p=0.010) and 17 (5 to 29, p<0.000) min/day more in non-TV sitting and total (accelerometry-measured) sedentary time, respectively. Associations across individual SEP components varied in strength. Area deprivation was not associated with sedentary time. Conclusions: Low SEP is linked with higher television times but with lower total (accelerometer-measured) sedentary time, and non-TV sitting during non-school time in children and adolescents. Associations between sedentary time and SEP differ by type of sedentary behaviour. TV viewing is not a good proxy for total sedentary time in children.